Optimizing Compilation Times for an Elixir Monolithic Codebase - Barbosa, Lívia Almeida (Anais do Workshop em Engenharia de Software para Programação Funcional (SE4FP); 2025: Anais do I Workshop em Engenharia de Software para Programação FuncionalDO - 10.5753/se4fp.2025.13530, 2025)
An inefficiently compiled codebase can harm the developer experience, the continuous integration process, and increase organizational costs. Addressing this problem may be challenging, requiring expertise and time to identify, resolve, and prevent the concerns. This paper presents how Remote manages the compilation time of its large-scale monolithic codebase.